DEVELOPMENT OF MELTED EXPANDED POLYSTYRENE AS ΒITUMEN MODIFIER FOR PAVEMENT CONSTRUCTION - AREMU TAJUDEEN ORIAJE; BAMIDELE IBUKUNOLU OLUGBEMI DAHUNSI; KAZEEM ADEKUNLE ADEYEMO (Journal of Engineering Studies and Research)
This study was designed to investigate the Performance of melted Expanded Polystrene (EPS) wastes on the quality of bitumen used in asphaltic concrete. The EPS materials were ground and then melted (200-400 oC) to form a slurry. Specific gravity of the EPS and chemical composition were determined by AAS analyses. The melted EPS was used as a modifier in mix proportions of 0, 2.5, 5, 7.5 and 10% by weight of bitumen. The 5% unmodified bitumen content obtained from the Marshall mix design was used to prepare asphalt concrete samples with 0 to 10% contents of melted EPS. The products were tested for Marshall stability, specific gravity, penetration, softening point, ductility, loss on heating, viscosity, flash and fire points and the melting point tests using standard methods. The ground EPS was uniform and well-graded (4.750-0.010 mm) with a specific gravity of 0.012, having a styrene structure with methanol on the ring. The specimen prepared with the specified mix proportion of EPS produced results that ranged between 5598.71-16937.70 N for Marshal stability; 2.02-3.54 for specific gravity; 129-152 mm for penetration; 42.80-47.50 oC for softening point; 75.00-32.90 cm for ductility; 0-3.48% for loss on heating; 208-2204 sec.STV for viscosity; 243.3-269.0 oC for flash point; 196.1-211.0 oC for melting point. The results also showed that with correlation coefficients ranging from r = 0.658-0.999, there is a strong positive correlation between the improvement exhibited in the specimen tested properties and melted EPS used in bitumen. At the 5% bitumen with 5% EPS by weight of asphalt concrete, the results of stability, flow and optimum bitumen content satisfied the British Standard Specification framework for polymer-modified bitumen and it is therefore suitable for flexible pavement construction.